Effects of glossy privet's invasion on the water dynamics of the Argentinean Yungas forest - Zamora Nasca, Lucía; Montti, Lia; Grau, Ricardo; Paolini, Leonardo (Bosque (Valdivia), 2017)
Argentinean Yungas (subtropical montane forests) have high biodiversity and play a key role in regional watershed regulation. Ligustrum lucidum (glossy privet), native of China, is one of the dominant exotic tree species in secondary forests of this ecoregion. Due to its high growth rates and green foliage throughout the year -in contrast to native forests which are partially deciduous- the hypothesis is that water availability is reduced in glossy privet forests, especially during dry season (winter-spring). Six pairs of plots both in native and secondary glossy privet dominated forests in Sierra San Javier, Tucumán, Argentina were sampled. Soil moisture, by measuring both volumetric water content and water potential, and estimated productivity of different types of forests, through normalized difference vegetation index (NDVI derived from satellite imagery), were monitored. During 2011 - 2012 dry seasons, soil volumetric water content in glossy privet forests was 32.5 % and 24 % lower than in native forests; while soil water potential was respectively eight and four times lower. In glossy privet forests NDVI values were 8.5 % higher than in native forests; particularly in lower altitude forests and those with a higher winter-spring water deficit. These results suggest that the glossy privet forest would be consuming more water, especially during the dry season, due to more prolonged phenology activity compared to native forests. In consequence, glossy privet invasion in Argentinean Yungas could alter water functioning of this ecosystem.